Performance Analysis by Organizational Culture and Motivation as Mediation, Influenced by Work Environment and Training - Aris Budiono; Indra Fahrizal (Yayasan Ilomata, 2023)
This research aims to confirm the effect of Work Environment and Training as exogenous variables by using Organizational Culture and Motivation as intervening variables on Performance. The quantitative method with three substructures is used. The population consists of 190 employees, 130 of which are researched using the Morgan table and 30 respondents are assigned to measure the validity and reliability. The results of this study reveal: work environment and training affect the variables of Organizational Culture, Motivation, and Performance; Training affects Organizational Culture and Motivation but not Performance variables; Organizational Culture Affects Performance, and Motivation does not affect Performance. Indirect effects: work environment variables affect Performance through organizational culture variables but do not affect Performance through Motivation. Training variables affect Performance through Organizational Culture but do not affect Performance through Motivation.